Characterization of Arabidopsis CYP79C1 and CYP79C2 by Glucosinolate Pathway Engineering in Nicotiana benthamiana Shows Substrate Specificity Toward a Range of Aliphatic and Aromatic Amino Acids - Wang, Cuiwei; Dissing, Mads Møller; Agerbirk, Niels; Crocoll, Christoph; Halkier, Barbara Ann (Frontiers in Plant Science, 2020)
Glucosinolates (GLSs) are amino acid-derived defense compounds characteristic of the Brassicales order. Cytochromes P450 of the CYP79 family are the entry point into the biosynthetic pathway of the GLS core structure and catalyze the conversion of amino acids to oximes. In Arabidopsis thaliana, CYP79A2, CYP79B2, CYP79B3, CYP79F1 and CYP79F2 have been functionally characterized and are responsible for the biosynthesis of phenylalanine-, tryptophan- and methionine-derived GLSs, respectively. However, the substrate(s) for CYP79C1 and CYP79C2 were unknown. Here, we investigated the function of CYP79C1 and CYP79C2 by transiently co-expressing the genes together with three sets of remaining genes required for GLS biosynthesis in Nicotiana benthamiana. Co-expression of CYP79C2 with either the aliphatic or aromatic core structure pathways resulted in the production of primarily leucine-derived 2-methylpropyl GLS and phenylalanine-derived benzyl GLS, along with minor amounts of GLSs from isoleucine, tryptophan and tyrosine. Co-expression of CYP79C1 displayed minor amounts of GLSs from valine, leucine, isoleucine and phenylalanine with the aliphatic core structure pathway, and similar GLS profile (except the GLS from valine) with the aromatic core structure pathway. Additionally, we co-expressed CYP79C1 and CYP79C2 with the chain elongation and aliphatic core structure pathways. With the chain elongation pathway, CYP79C2 still mainly produced 2-methylpropyl GLS derived from leucine, accompanied by GLSs derived from isoleucine and from chain-elongated mono- and dihomoleucine, but not from phenylalanine. However, co-expression of CYP79C1 only resulted in GLSs derived from chain-elongated amino acid substrates, dihomoleucine and dihomomethionine, when the chain elongation pathway was present. This shows that CYP79 activity depends on the specific pathways co-expressed and availability of amino acid precursors, and that description of GLS core structure pathways as “aliphatic” and “aromatic” pathways is not suitable, especially in an engineering context. This is the first characterization of members of the CYP79C family. Co-expression of CYP79 enzymes with engineered GLS pathways in N. benthamiana is a valuable tool for simultaneous testing of substrate specificity against multiple amino acids.